Increased Expression of sST2 in Early HIV Infected Patients Attenuated the IL-33 Induced T Cell Responses - Wu, Xian; Li, Yao; Song, Cheng-Bo; Chen, Ya-Li; Fu, Ya-Jing; Jiang, Yong-Jun; Ding, Hai-Bo; Shang, Hong; Zhang, Zi-Ning (Frontiers in Immunology, 2018)
T cell responses were less functional and persisted in an exhausted state in chronic HIV infection. Even in early phase of HIV infection, the dysfunction of HIV-specific T cells can be observed in rapid progressors, but the underlying mechanisms are not fully understood. Cytokines play a central role in regulating T cell function. In this study, we sought to elucidate whether IL-33/ST2 axis plays roles in the regulation of T cell function in HIV infection. We found that the level of IL-33 was upregulated in early HIV-infected patients compared with that in healthy controls and has a trend associated with disease progression. In vitro study shows that IL-33 promotes the expression of IFN-γ by Gag stimulated CD4+ and CD8+T cells from HIV-infected patients to a certain extent. However, soluble ST2 (sST2), a decoy receptor of IL-33, was also increased in early HIV infected patients, especially in those with progressive infection. We found that anti-ST2 antibodies attenuated the effect of IL-33 to CD4+ and CD8+T cells. Our data indicates that elevated expression of IL-33 in early HIV infection has the potential to enhance the function of T cells, but the upregulated sST2 weakens the activity of IL-33, which may indirectly contribute to the dysfunction of T cells and rapid disease progression. This data broadens the understanding of HIV pathogenesis and provides critical information for HIV intervention.